Corals in the hottest reefs in the world exhibit symbiont fidelity not flexibility. Issue 5 (17th February 2020) - Howells, Emily J.; Bauman, Andrew G.; Vaughan, Grace O.; Hume, Benjamin C. C.; Voolstra, Christian R.; Burt, John A.
Abstract: Reef‐building corals are at risk of extinction from ocean warming. While some corals can enhance their thermal limits by associating with dinoflagellate photosymbionts of superior stress tolerance, the extent to which symbiont communities will reorganize under increased warming pressure remains unclear. Here we show that corals in the hottest reefs in the world in the Persian Gulf maintain associations with the same symbionts across 1.5 years despite extreme seasonal warming and acute heat stress (≥35°C). Persian Gulf corals predominantly associated with Cladocopium (clade C) and most also hosted Symbiodinium (clade A) and/or Durusdinium (clade D). This is in contrast to the neighbouring and milder Oman Sea, where corals associated with Durusdinium and only a minority hosted background levels of Cladocopium . During acute heat stress, the higher prevalence of Symbiodinium and Durusdinium in bleached versus nonbleached Persian Gulf corals indicates that genotypes of these background genera did not confer bleaching resistance. Within symbiont genera, the majority of ITS2 rDNA type profiles were unique to their respective coral species, confirming the existence of host‐specific symbiont lineages. Notably, further differentiation among Persian Gulf sites demonstrates that symbiont populations are either isolated or specialized over tens to hundreds of kilometres. Thermal tolerance across coral species was associated with the prevalence of a single ITS2 intragenomic sequence variant (C3gulf), definitive of the Cladocopium thermophilum group. The abundance of C3gulf was highest in bleaching‐resistant corals and at warmer sites, potentially indicating a specific symbiont genotype (or set of genotypes) that may play a role in thermal tolerance that warrants further investigation. Together, our findings indicate that co‐evolution of host–Symbiodiniaceae partnerships favours fidelity rather than flexibility in extreme environments and under future warming.